Heat stress induced by testicular insulation for 24 or 48 h rapidly impairs epididymal sperm quality and reduces spermatogenesis in rams - Teixeira, Marina Belucci [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Codognoto, Viviane Maria [UNESP]; Rossi, Eduardo Santos [UNESP]; Pupulim, Antonio Guilherme Roncado [UNESP]; de Carvalho, Jaqueline Cândido [UNESP]; Rattes, Paula Zanin [UNESP]; Oba, Eunice [UNESP]; Navolar, Felipe Martins Negreiro; Di Santis, Giovana Wingeter; Kastelic, John Patrick; Van Soom, Ann; et al. (Elsevier, 2025)
Mammalian testes must be 3–5 ºC below body core temperature to produce morphologically normal sperm. The objective was to investigate impacts of heat stress (HS) induced by scrotal insulation on epididymal sperm and temporal aspects of HS on spermatogenesis. We hypothesized that: (1) increased testicular temperature impairs sperm in the epididymis; and (2) spermatids are severely impacted by HS exposure. Testicular HS was induced by scrotal insulation for 24 or 48 h in 20 reproductively sound adult rams, with 5 similar rams designated controls (not insulated). Rams were castrated at 24 h, 48 h, 7 d, or 14 d after the start of insulation (whereas control rams were randomly castrated). Insulation increased scrotal surface temperature by ∼5 ºC. There were marked decreases (P < 0.01) in sperm motility, progressive motility and kinetics starting at 24 h and sustained throughout the study. Percentage of epididymal sperm with normal morphology first decreased at 24 h (P < 0.01) with subsequent decreases at 48 h (P < 0.01) and 7 d (P < 0.01); thereafter, morphology remained stable (P > 0.05). At 14 d, there were decreases in testicular weight (P < 0.05) and seminiferous tubule diameter (STD) (P < 0.001) when compared to all other groups. Regarding seminiferous tubule integrity (Johnsen's score), a first decrease occurred at 24 h (P < 0.05) followed by a more intense decrease at 14 d (P < 0.001). In addition, there was an abrupt decrease (P < 0.05) in spermatid counts at 24 h that was sustained throughout the study. In conclusion, our hypotheses were supported; testicular HS caused immediate deleterious impacts on epididymal sperm at 24 and 48 h post-insulation as well as developing spermatids at 7 and 14 d, decreasing sperm production and significantly reducing both STD and testicular weight.
Keywords: Seminiferous tubule; Sperm morphology; Sperm motility; Testicular hyperthermia; Testis